Mô hình và phương pháp tính toán độ bền bệ toa xe khi chiu lực va đập dọc - Lê, Văn Học (Bộ Giáo dục và Đào tạo, 2013)
It is informed in the article about setting up of the calculation modul for wagon underframe under longitudinal impact forces with all beams and small angle stells of the underframe, the Load is dynamic load depended on the impact velocity of wagon, structure data and working charaterictics for the couple of each wagon. The differential equation system discribed the Oscilation of backbone beam; .begining, boundary and limit condition of the probem Applying of the above modul to solve longitudinal impact problem between two high-side wall wagons by the numerical integral method of differential equations. The obtained resuldt is longitudinal tension diagram along th backbone beam which depended on the impact velocity between two wagons.